Reforma Agraria Upaya Penyelesaian Konflik Tanah di Kecamatan Jenggawah Kabupaten Jember Tahun 1999-2005 - Mohamad Il Badri (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
The purpose of this paper is to determine the process of resolving agrarian conflicts and the process of inventorying and granting land certificates to farmers. The urgency of this paper can theoretically be an important part in the context of resolving agrarian conflicts that often occur in Indonesia. The method used is the historical method consisting of Heuristics, Criticism, Interpretation and Historiography. Agrarian conflicts in Jenggawah District, Jember Regency occurred in 1969 and 1994-1995. The government is trying to find a solution through the implementation of agrarian reform by providing a policy for solving agrarian problems. Efforts to resolve the Jenggawah land conflict through agrarian reform are marked by a process of preparing for the implementation of an inventory, asset management and access arrangement. Asset management consists of redistribution and legalization of land. Access arrangements are carried out in order to improve the economy, add value and encourage entrepreneurial innovation on the subject of agrarian reform for Jenggawah farmers. Through this research, it can be concluded that agrarian reform can be one of the solutions for resolving land conflicts in Indonesia, especially in Jenggawah.